The embodiment of craft production in Bronze Age Portugal: Exceptional dental wear grooves in an individual from Monte do Vale do Ouro 2 (Ferreira do Alentejo, Portugal) - Willman, John Charles (2021)
Two human lateral mandibular incisors exhibiting exceptional dental wear in the form of lingual surface grooves along the cementoenamel junction were recovered from the superficial levels of a pit grave attributed to the Bronze Age at the archaeological site of Monte do Vale do Ouro 2 (Ferreira do Alentejo, Beja, Portugal). Although a number of analyses of dental wear features acknowledge the relatively common use of the dentition for non-dietary purposes (using the “teeth as tools”) during the Early/Middle Bronze Age (2200–1200 BC) of southwest Iberia, the form of dental wear documented at Monte do Vale do Ouro 2 is not only a novel finding in this region, but has seldom been described in any bioarchaeological context. The present study provides a macroscopic and low-magnification description of the atypical dental wear for this individual. Results indicate that the incisors are likely antimeres. In addition to the deep lingual grooves, asymmetrical wear removed a substantial portion of the laterolingual crown volume of each tooth. Occlusal and lingual surface wear accumulated slowly enough for tertiary dentin to form. An occlusal groove is also present on the right I2. A review of ethnohistoric and bioarchaeological literature suggests that some form of craft production involving the manipulation of cordage or fiber with the mouth and teeth can account for the unique wear patterns from Monte do Vale do Ouro 2. The hand-spinning of flax requires wetting which can be accomplished by passing flax fibers through the mouth in a mediolateral direction while using